The potential of using temperate–tropical crossbreds and agricultural by-products, associated with heat stress management for dairy production in the tropics: a review - Michael, Predith; De Cruz, Clement Roy; Mohd Nor, Norhariani; Jamli, Saadiah; Goh, Yong Meng (Multidisciplinary Digital Publishing Institute, 2022)
The demand and consumption of dairy products are expected to increase exponentially in developing countries, particularly in tropical regions. However, the intensification of dairy production to meet this increasing demand has its challenges. The challenges ranged from feed costs, resources, and their utilization, as well as the heat stress associated with rearing temperate–tropical crossbred cattle in the tropics. This article focused on key nutritional and environmental factors that should be considered when temperate–tropical crossbred cattle are used in the tropics. The article also describes measures to enhance the utilization of regional feed resources and efforts to overcome the impacts of heat stress. Heat stress is a major challenge in tropical dairy farming, as it leads to poor production, despite the genetic gains made through crossbreeding of high production temperate cattle with hardy tropical animals. The dependence on imported feed and animal-man competition for the same feed resources has escalated feed cost and food security concerns. The utilization of agricultural by-products and production of stable tropical crossbreds will be an asset to tropical countries in the future, more so when scarcity of feed resources and global warming becomes a closer reality. This initiative has far-reaching impacts in the tropics and increasingly warmer areas of traditional dairying regions in the future.